NERACA AIR LAHAN UNTUK PENGEMBANGAN TANAMAN KELAPA SAWIT (Elaeis guinensis Jacq), DI KECAMATAN SANGKUB, KABUPATEN BOLAANG MONGONDOW UTARA - Silvana E. Kaeng; Johannes E.X. Rogi; Jantje ., Pongoh (Sam Ratulangi University, 2017)
This study aims to find out the water balance in Sangkub Sub-district, North Bolaang Mongondow Regency for oil palm cultivation with water balance simulation model developed by Handoko (1994) and Rogi (2002). The study was conducted from May - December 2016. This research uses simulation model method; the data used in this research is secondary data. The data analysis used run model of water balance of land and formula calculation of land water balance. The study found that the amount of water surplus from the run of the water balance model and calculations based on the formula in one year cannot meet the water requirements of oil palm crops, so that oil palm plantations cannot be cultivated in Sangkub Sub-district. This is due to the existence of rice cultivated crops prior to oil palm cultivation, where both plants require relatively large amount of water.